2009
DOI: 10.1073/pnas.0909109106
|View full text |Cite
|
Sign up to set email alerts
|

FM dyes enter via a store-operated calcium channel and modify calcium signaling of cultured astrocytes

Abstract: The amphiphilic fluorescent styryl pyridinium dyes FM1-43 and FM4-64 are used to probe activity-dependent synaptic vesicle cycling in neurons. Cultured astrocytes can internalize FM1-43 and FM4-64 inside vesicles but their uptake is insensitive to the elevation of cytosolic calcium (Ca 2؉ ) concentration and the underlying mechanism remains unclear. Here we used total internal reflection fluorescence microscopy and pharmacological tools to study the mechanisms of FM4-64 uptake into cultured astrocytes from mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…It was reported that the endocytic dye FM4-64, a pyridinium analogue of considerably larger size than APP+, is taken up by cortical astrocytes via store-operated Ca 2+ entry (SOCE) channels. 49 It was also suggested that background staining in brain slice observed with FM4-64 might be due to astrocytic uptake occurring via the SOCE channels. Organic cation transporters such as OCT3, which are widely expressed in the brain and have been shown to transport MPP+, 50,51 may also contribute to extracatecholaminergic staining by APP+.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It was reported that the endocytic dye FM4-64, a pyridinium analogue of considerably larger size than APP+, is taken up by cortical astrocytes via store-operated Ca 2+ entry (SOCE) channels. 49 It was also suggested that background staining in brain slice observed with FM4-64 might be due to astrocytic uptake occurring via the SOCE channels. Organic cation transporters such as OCT3, which are widely expressed in the brain and have been shown to transport MPP+, 50,51 may also contribute to extracatecholaminergic staining by APP+.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A single, stable population of terminals before and after LTP It is important to verify that sampled puncta were primarily representative of CA3 terminals, and did not include large numbers of GABAergic inhibitory interneurons or astrocytes, both of which endocytose FM 1 -43 (Hablitz et al 2009;Li et al 2009) and are frequently overlooked in hippocampal FM experiments. If this were the case, one might expect different populations of destaining kinetics to be apparent in our data, as both inhibitory interneurons and astrocytes exhibit heterogeneity in their release properties (McBain and Fisahn 2001;Moulder et al 2007;Sakaba 2008).…”
Section: Ltp2 and Ltp3 Involve Enhanced Presynaptic Functionmentioning
confidence: 99%
“…been reported to label hair cells of lateral line organs [2,[11][12][13][14][15][16][17][18][19][20] and the inner ear [19,[21][22][23][24][25][26][27][28][29]. Other sensory cells and nerves are also labeled with FM1-43, AM1-43 and related dyes: vibrissal follicles, palatal rugae, enteric neurons, nasal mucosa, Merkel cells, muscle spindles, cultured astrocytes, sensory neurons of trigeminal and dorsal root ganglia, sensory receptors of visceral pleura, and cough receptors of vagal sensory neurons [22,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 91%
“…Although astrocytes are not sensory neurons, the FM1-43-related dye FM4-64, enters a store-operated calcium channel of cultured astrocytes [37]. Karashima et al [61] reported on the other channel of transient receptor potential (TRP) family that TRPA1-transfected Chinese hamster ovary (CHO) cells are labeled with FM1-43 following stimulation with a TRPA1 agonist.…”
Section: Labeling Through Sensory Cation Channelsmentioning
confidence: 98%